Genotypic Profiling of Bacillus cereus Recovered from Some Retail Foods in Ogun State, Nigeria, and Their Phylogenetic Relationship - Titilayo O. Adesetan; Moses O. Efuntoye; Olubukola O. Babalola (International Journal of Microbiology)
Identifying Bacillus cereus with conventional methods is neither specific nor rapid because of the close relatedness of the B. cereus group, hence the need for molecular methods. Genotypic profiling of B. cereus isolates from food was obtained by Random Amplified Polymorphic DNA-polymerase chain reaction (RAPD-PCR) using OPR13 primer. A dendrogram was drawn with the Numerical Taxonomy System of Statistic (NTSYS) software. Thirty of the isolates were subjected to molecular identification by 16S rDNA sequencing. The thirty sequences were deposited in GenBank for accession number. Phylogenetic relationship of the 16S rDNA sequence obtained was carried out with the Multiple Alignment using Fast Fourier Transform (MAFFT) software version 7.0. The evolutionary tree was drawn using the Molecular Evolutionary Genetics Analysis (MEGA 6) software. The dendrogram generated for the RAPD profile showed that all the strains are closely related, with a similarity coefficient of 70%. The isolates were confirmed with 16S rDNA sequencing as B. cereus. The thirty sequences deposited in GenBank were given accession numbers: KX574760–KX574769, KX610811–KX610820, MT757957-MT757963, and MT772282-MT772284. By comparing the phylogenetic relationship, eleven of the strains did not cluster with the reference strains from the GenBank but form distinct clades, which means they are likely to be of different ancestors. Conventional methods rarely differentiate bacteria of the same species into clade, neither can it describe their ancestral lineage. Therefore, it is important to employ molecular methods in identifying bacteria to give detailed information about them.